The text of the Old Testament in Anglo-Saxon England - Marsden, Richard (Cambridge Univ. Press, 1995)
The early medieval Vulgate Bible had no fixed textual form - multiple copying resulted in a multitude of forms. Examination of the complex patterns of variation may illuminate important aspects of monastic, ecclesiastical and intellectual history. This book is the first to tackle questions about the transmission of the Vulgate Old Testament in Anglo-Saxon England. Following an introduction which explains the wider continental context in which the dissemination of the Latin scriptures occurred, Richard Marsden goes on to analyse twenty surviving Anglo-Saxon manuscripts including the Codex Amiatinus, one of the greatest English books and the earliest surviving complete Vulgate Bible. A further chapter examines the evidence of the earliest translations of scripture into Old English. Dr Marsden's study presents the first comprehensive listing and collation of Anglo-Saxon manuscripts of the Old Testament and affirms the importance of textual history as a dimension of wider Anglo-Saxon history.
Keywords: Bible. -- O.T. -- English (Old) -- Versions; Bible. -- O.T. -- Latin -- Versions -- Vulgate; Bible. -- O.T. -- Criticism, Textual; Bible. -- O.T. -- Manuscripts; Bibel -- Altes Testament; Bibel -- Vulgata; Geschichte 550-1050; Oude Testament; Oudengelse handschriften; Vertalingen; Bibel. Altes Testament; Geschichte; Latin language -- Translating into English -- History -- To 1500; Manuscripts, English (Old); Manuscripts, Medieval -- England; Handschrift; Altenglisch; Textgeschichte; England